(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article determined that the principles of ensuring the rights, freedoms and legitimate interests of citizens by local self-government bodies in Ukraine under martial law direct administrative decisions, legislative initiatives, public projects in the studied sphere of public relations in a clearly defined vector, outlined taking into account the provisions of the legislation, problems of law enforcement, as well as current trends in domestic science, in particular in the field of public administration. It was noted that the principle of interaction between central and local authorities under martial law underlies the timely interaction of municipal services with bodies and units of the National Police of Ukraine, the State Emergency Service of Ukraine and other bodies and units, which allows for the prompt saving of human lives. It is argued that the basis for considering the principle of regional specificity is the development by individual local government bodies and their associations of strategies dedicated to the comprehensive solution of existing problems, highlighting relevant legal issues that they encounter in their daily activities, discussing them, developing solutions and disseminating them within the regions and the entire state. It is noted that the implementation of the principle of maximum approximation to the real needs of the community requires the necessary number of specialists ready to work in territorial communities, and the appropriate level of their professional competence.